Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1177/1545968309338191
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Between Electromyography-Driven Robot and Passive Motion Device on Wrist Rehabilitation for Chronic Stroke

Abstract: . A comparison between electromyography-driven robot and passive motion device on wrist rehabilitation for chronic stroke. Neurorehabilitation and Neural Repair, 23(8) This is the Pre-Published Version.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
156
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(160 citation statements)
references
References 23 publications
(53 reference statements)
4
156
0
Order By: Relevance
“…Furthermore, learning in TIFT was disjointed early in the training, with subjects often hitting the path walls, stopping and trying several strategies before determining the correct shoulder-elbow coordination needed to advance within the path. Nevertheless, for stroke rehabilitation, we believe further study into assistance modes such as TIFT is needed, given the recent negative findings in robots that have used the TD training mode [42][43] and the evidence that passive movement training does not improve motor control [82][83]. For example, Bluteau et al found that in a drawing task, haptic guidance with a position-based controller similar to our TD training mode was inferior to a force-based controller for motor learning [84].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, learning in TIFT was disjointed early in the training, with subjects often hitting the path walls, stopping and trying several strategies before determining the correct shoulder-elbow coordination needed to advance within the path. Nevertheless, for stroke rehabilitation, we believe further study into assistance modes such as TIFT is needed, given the recent negative findings in robots that have used the TD training mode [42][43] and the evidence that passive movement training does not improve motor control [82][83]. For example, Bluteau et al found that in a drawing task, haptic guidance with a position-based controller similar to our TD training mode was inferior to a force-based controller for motor learning [84].…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiology experiments have demonstrated that afferent feedback can facilitate plasticity in the motor system if it arrives synchronously with ongoing motor output [59][60]. This has motivated a number of robotic strategies to assure proper timing between effort and movement, including movement of the contralateral limb to control movement of the paretic limb in bilateral tasks [32,[85][86] and EMG-controlled movement [83,[87][88]. The TIFT mode assures proper timing between effort and movement by presenting a passive environment to the limb, such that no energy is injected into the limb.…”
Section: Discussionmentioning
confidence: 99%
“…The hand contains 16 joints, which are differentially driven by a set of five independent actuators. Hu et al (2009) have presented a comparison between electromyography-driven robot and passive motion device on wrist rehabilitation for chronic stroke patients. By comparative study, it was found that the EMG-driven interactive training had a better long-term effect than the continuous passive movement (CPM) treatment.…”
Section: Prior Research Related To Emg Applicationsmentioning
confidence: 99%
“…Application of robot-assisted arm training in patients with Parkinson's disease was recently reported in [9]. A comparison between EMG-driven and passive devices used on wrist rehabilitation with chronic stroke patients is presented in [10], proving interactive training to be superior to passive training.…”
Section: Introductionmentioning
confidence: 99%